Effectiveness of Using the Indonesian Standard Quick Response Code (QRIS) to Ease Transactions at Paddy's Market, Kendari City - Muhammad Rusydi Navri; Syahriyah Semaun; Damirah; Muliati; Muhammad Kamal Zubair (Universitas Muhammadiyah Palu, 2024)
The Kendari City Government began to socialise the implementation of the Healthy, Innovative, Safe, Use (S.I.A.P.) QRIS Market and Safe Program with Bank Indonesia, Himbara in several Kendari City Markets. Paddy's Market is one of the markets that has been facilitated with the QRIS payment system. However, in practice it is not as easy as discussed in theory, the majority of traders in Paddy's Market no longer use the QRIS that has been given with the main reason being the lack of understanding of traders and buyers of the QRIS Payment system. The purpose of this study is to analyse how effective the use of QRIS is in Kendari City Paddy's Market. This research uses a qualitative descriptive method that takes information through interviews. Data collection was obtained through interviews with traders and buyers at Paddy's Market Kendari City. The results of this study indicate that: : (1) The practice of using QRIS in Kendari City Paddy's Market is decreasing, many traders have started to stop using QRIS, some have not used it at all since the launch of the QRIS programme. This is due to the lack of understanding of traders or buyers in using the QRIS feature, lack of control from Bank Indonesia, City Government, related banks so that traders and buyers no longer use QRIS and switch to cash transactions as usual. (2) Various obstacles, and reasons so that the majority of traders and buyers in the market use cash more often than QRIS.